Life Cycle Assessment and Environmental Load Management in the Cement Industry - Qiang Su; Ruslan Latypov; Shuyi Chen; Lei Zhu; Lixin Liu; Xiaolu Guo; Chunxiang Qian (Systems)
The cement industry is a significant contributor to global environmental impacts, and Life Cycle Assessment (LCA) has emerged as a critical tool for evaluating and managing these burdens. This review uniquely synthesizes recent advancements in the LCA methodology and provides a detailed comparison of cement production impacts across major producing regions, notably highlighting China’s role as the largest global emitter. It covers the core LCA phases, including goal and scope definition, inventory analysis, impact assessment, and interpretation, and emphasizes the role of LCA in quantifying cradle-to-gate impacts (typically around 0.9–1.0 t CO2 per ton of cement), evaluating the emissions reductions provided by alternative cement types (such as ~30–45% lower emissions using limestone calcined clay cements), informing policy frameworks like emissions trading schemes, and guiding sustainability certifications. Strategies for environmental load reduction in cement manufacturing are quantitatively examined, including technological innovations (e.g., carbon capture technologies potentially cutting plant emissions by up to ~90%) and material substitutions. Persistent methodological challenges—such as data quality issues, scope limitations, and the limited real-world integration of LCA findings—are critically discussed. Finally, specific future research priorities are identified, including developing country-specific LCI databases, integrating techno-economic assessment into LCA frameworks, and creating user-friendly digital tools to enhance the practical implementation of LCA-driven strategies in the cement industry.